The Effect of NPK Fertilizer and Fertilizer Through Leaves on the Growth and Yield of Red Chili (Capsicum annum L) - Budi Prastia (Baselang, 2022)
Research on the effect of NPK fertilizer and fertilizer application through leaves on the growth and yield of red chili (Capsicum annum L) was carried out from October 2021–March 2022 on farmer lands in Tanah Grow Village, Tanah Grow District, Bungo Regency. With the aim of knowing the interaction between NPK fertilizer and fertilizer through leaves on the growth and yield of red chili plants. This experiment was conducted in a completely randomized design in the form of factorial with two factors and repeated 3 times. Factor A is the dose of NPK fertilizer which consists of 4 levels, namely: NI = 5 gr, N2 = 10 gr, N3 = 15 gr, N4 = 20 gr .Factor B is the provision of fertilizer through the leaves (Seprint), namely: PI = 8 cc/ltr, P2 = 10 cc/ltr, P3 = 12 cc/ltr, P4 = 14 cc/ltr, P5 = 16 cc/ltr. Based on the experiment, it can be concluded that there was an interaction between NPK fertilizer and Seprint leaf fertilizer on the yield of red chili plants, while there was no interaction with plant height, number of leaves and number of productive branches. The application of NPK fertilizer with a dose of N3 = 15 grams gave the best results on red chili crop yields. In the use of fertilizer through leaves (Seprint) the best concentration was 10 cc/liter, for plant height. Provision of NPK fertilizer and fertilizer through leaves (Seprint) had no significant effect on the parameters of the number of leaves and the number of productive branches.